Comparison of thiocyanate and selenocyanate for potentiation of antimicrobial photodynamic therapy. Issue 1 (3rd August 2018) - Huang, Liyi; Xuan, Weijun; Sarna, Tadeusz; Hamblin, Michael R.
Abstract : We have previously shown that antimicrobial photodynamic therapy (aPDT) mediated by different photosensitizers (PS) can be potentiated by a variety of inorganic salts. Potassium thiocyanate (KSCN) potentiated aPDT mediated by methylene blue (MB), while potassium selenocyanate (KSeCN) potentiated aPDT mediated by MB, Rose Bengal and the anionic porphyrin 5, 10, 15, 20‐tetrakis(4‐sulfonatophenyl)porphyrin dihydrochloride. However, the mechanisms of action that were proposed were fundamentally different. In the present study, we compare these two salts (KSCN and KSeCN) with different light‐activated PS and different oxidative reactions for killing gram‐positive and gram‐negative bacteria. Overall KSeCN was more powerful than KSCN, and worked with a wider range of PS, while KSCN only worked with phenothiazinium salts. KSeCN produced killing when cells were added after light suggesting production of a semistable species called selenocyanogen (SeCN)2 . We tested three different oxidative reactions that can all potentially kill bacteria: lead tetraacetate (Pb[OAc]4 ); Fenton reagent (hydrogen peroxide [H2 O2 ] and ferrous sulfate) H2 O2 and horseradish peroxidase (HRP). In every case, KSeCN was substantially more effective (several logs) than KSCN in potentiating the bacterial killing. We conclude that (SeCN)2 is the mediator for aPDT using KSeCN, while sulfur trioxide radical anion is the mediator for KSCN using phenothiaziums. For H2 O2 /HRP with KSCN, hypothiocyanite is proposed to be the antibacterial agent in the literature, while hyposelenocyanite is said not to exist. Pb[OAc]4 is known to produce (SeCN)2 from KSeCN as well as the analogous (SCN)2 from KSCN. The mediators from Fenton reaction are unclear (pseudohalogen radical ions?) Both KSCN (which occurs naturally in the human body) and KSeCN may be clinically applicable. Abstract : We compare the effects and mechanisms of the potentiation of antimicrobial photodynamic inactivation by addition of two inorganic salts, potassium selenocyanate and potassium thiocyanate. Selenocyanate was better and also worked with other oxidative reactions. Mechanisms include the formation of selenocyanogen, thiocyanogen, sulfur trioxide radical anion and hypothiocyanite.